6.5x-3.44=5.2-4.3x

Simple and best practice solution for 6.5x-3.44=5.2-4.3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6.5x-3.44=5.2-4.3x equation:


Simplifying
6.5x + -3.44 = 5.2 + -4.3x

Reorder the terms:
-3.44 + 6.5x = 5.2 + -4.3x

Solving
-3.44 + 6.5x = 5.2 + -4.3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4.3x' to each side of the equation.
-3.44 + 6.5x + 4.3x = 5.2 + -4.3x + 4.3x

Combine like terms: 6.5x + 4.3x = 10.8x
-3.44 + 10.8x = 5.2 + -4.3x + 4.3x

Combine like terms: -4.3x + 4.3x = 0.0
-3.44 + 10.8x = 5.2 + 0.0
-3.44 + 10.8x = 5.2

Add '3.44' to each side of the equation.
-3.44 + 3.44 + 10.8x = 5.2 + 3.44

Combine like terms: -3.44 + 3.44 = 0.00
0.00 + 10.8x = 5.2 + 3.44
10.8x = 5.2 + 3.44

Combine like terms: 5.2 + 3.44 = 8.64
10.8x = 8.64

Divide each side by '10.8'.
x = 0.8

Simplifying
x = 0.8

See similar equations:

| 18+4(5c-2)= | | 3/4=-2/3-5/6x | | (3x/4)=(6/7) | | 7y-4+2y=6y+11 | | 2.7=16/x | | (a)(.08)+a=145.8 | | -7x+3=-10+2 | | 6x+(3x+9)=180 | | 5x+34-25=17 | | -(4-8x)+8x=6x+26 | | 4+3x=7x-12 | | (24z^3-6z^2)/(3z^2) | | (1/2)x-37=-84 | | 4x-2(6+2x)=5 | | 4x+5x+5=6x-10 | | 3/4+1/3*x=2/4 | | 7-3x=35 | | 2(x+1)=4x+8 | | 115+n+5=180 | | 16x-7=-4x+13 | | (-14)+(-36)= | | x+3x=58+6 | | a-15=-4(-6+3a) | | 5/3*x+1/3*x=2x+21/3+7/3*x | | 3g=33 | | 7g-6=22 | | 250+14=22x | | xa+xb-7=4 | | ax+bx-7=4forx | | 1.3z-5=3z+3.5 | | log(6-2k)=log-k | | 5-(t+3)=-1+2t-6 |

Equations solver categories